Can Housing Risk Be Diversified? A Cautionary Tale from the Housing Boom and Bust - Cotter, John; Gabriel, Stuart; Roll, Richard (Review of Financial Studies, 2015)
This study evaluates the effectiveness of geographic diversification in reducing housing investment risk. To characterize diversification potential, we estimate spatial correlation and integration among 401 U.S. metropolitan housing markets. The 2000s boom brought a marked uptrend in housing market integration associated with eased residential lending standards and rapid growth in private mortgage securitization. As boom turned to bust, other macroeconomic factors, including employment and income fundamentals, importantly contributed to the trending up in housing return integration. Portfolio simulations reveal substantially lower diversification potential and higher risk in the wake of increased market integration.